Preclinical pharmacology of perampanel, a selective non‐competitive AMPA receptor antagonist. (11th March 2013) - Rogawski, M. A.; Hanada, T.
Abstract : Perampanel [2‐(2‐oxo‐1‐phenyl‐5‐pyridin‐2‐yl‐1, 2‐dihydropyridin‐3‐yl)benzonitrile; E2007] is a potent, selective, orally active non‐competitive AMPA receptor antagonist developed for the treatment of epilepsy. Perampanel has a 2, 3′‐bipyridin‐6′‐one core structure, distinguishing it chemically from other AMPA receptor antagonist classes. Studies in various physiological systems indicate that perampanel selectively inhibits AMPA receptor‐mediated synaptic excitation without affecting NMDA receptor responses. Blocking of AMPA receptors occurs at an allosteric site that is distinct from the glutamate recognition site. Radioligand‐binding studies suggest that the blocking site coincides with that of the non‐competitive antagonist GYKI 52466, believed to be on linker peptide segments of AMPA receptor subunits that transduce agonist binding into channel opening. As is typical for AMPA receptor antagonists, perampanel exhibits broad‐spectrum antiseizure activity in diverse animal seizure models. Perampanel has high oral bioavailability, dose‐proportional kinetics, and undergoes oxidative metabolism, primarily via CYP3A4, followed by glucuronidation. The terminal half‐life ( t ½ ) in humans is 105 h; however, in the presence of a strong CYP3A4 inducer (such as carbamazepine), the t ½ can be reduced. In sum, perampanel is a selective, centrally acting, negative allosteric modulator of AMPA receptors with good oral bioavailability and favorable pharmacokinetic properties.